SyTroN: A Virtual Classroom for Collaborative and Distant E-Learning System by Teleoperating Real Devices. (18th May 2009) - Chellali, R.; Dumas, C.; Mollet, Nicolas; Subileau, G.
Abstract : Distant E-learning is a main issue nowadays, and it is strongly motivated by social and economical considerations. The increased people mobility and the reduction of educational costs push to develop ad hoc solutions enabling to access to knowledge regardless to geographical situation and economical capabilities. These parameters should not be limits for good training: learning material's pertinence and efficiency have to remain the core of educational activities. In this paper we address the problem through SyTroN: a tele-learning system. This system combines virtual reality and teleoperation techniques to offer an open platform with two main objectives. The first one is to propose intuitive virtual classrooms/desks, including a real teacher supervision and supporting collaborative and individual distant learning. The second goal is to place learners in real conditions with remote connections to real devices allowing distant experimentations. Both goals participate to increase learning impacts and to reduce costs, that is, sharing costly real devices from anywhere at any time. After 5 years of development, our work has been validated by an extensive use at a high engineering school. In situ tests and learning impact studies have been done. They show some advantages and some drawbacks of our global solution.